Dark tribute - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller., 2019)
New York Times bestseller Iris Johansen is back with another high octane thriller that will leave your mind racing and your heart pounding. Despite her tragic childhood, violin prodigy Cara Delaney has finally found peace in her career as a professional musician and stability in her relationship with her guardians, forensic sculptor Eve Duncan and ex-Navy SEAL Joe Quinn. If only Jock Gavin, Cara's lifelong friend and a man with his own twisted history, would even talk to her, everything would be perfect. But the carefully constructed life Cara has built for herself is suddenly threatened when she is kidnapped by a mysterious man from her grandfather's past, setting off a violent chain of events that puts everyone Cara loves in danger. Will Cara become a tribute to her family's dark past, or will she be able to keep herself and her loved ones alive? Praise for Iris Johansen: "A tantalizing puzzle...fans of paranormal suspense will be rewarded." --Publishers Weekly "A fun read filled with plenty of action and mystery...Eve Duncan did not disappoint!" --Criminal Element on Shattered Mirror "A fun plot...charming." --Kirkus on Shattered Mirror